Gas Flow Characteristics through Irregular Particle Bed with the Vertical Confined Wall for Waste Heat Recovery - Sizong Zhang; Zhi Wen; Xunliang Liu; Yi Xing; Hui Zhang (International Journal of Photoenergy)
The vertical waste heat recovery technology of the sinter in the iron and steel industry will be a great driving force for China to realize the “double Carbon” in the near future. For promoting the application of the new technology, the influence of the confined wall on the pressure distribution and pressure drops of the gas flow in the sinter bed was experimentally studied. For the irregular sinter with the rough surface, the gas pressure near the wall is higher than that at the center. Moreover, the radial distribution of the dimensionless pressure is nearly the same at different gas velocities. Therefore, whatever flow state the gas is in, the wall effect on irregular sinters only reduces the pressure drop of the gas flow, which is different from that on spherical particles. The vertical wall limits the randomness and uniformity of the particle accumulation, which is further intensified with the increase of the particle irregularity and particle size. Therefore, the confined wall causes a greater difference in the gas pressure between the wall and the center. With the particle size increasing from 5~10 mm to 55~60 mm, the ratio of the gas pressure between the wall and the center increases from 1.03 to 1.26. If the wall effect is ignored, the pressure drop of the gas flow would be overestimated by 16.01% on average, whereas the correlation of the wall correction can well predict the pressure drop with the mean error and maximum error of 2.74% and 9.48%, respectively.